Measuring well-being by a multidimensional spatial model in OECD Better Life Index framework. (June 2020) - Greco, Salvatore; Ishizaka, Alessio; Resce, Giuliano; Torrisi, Gianpiero
Abstract: One of the most influential measures of multidimensional well-being, the Better Life Index, launched by OECD in 2011, contains a detailed overview of the social, economic, and environmental performances of different countries. Since its launch, a relevant number of empirical studies have been proposed on these data, but the role played by the distance between societal priorities and country-level performance in Better Life Index as well as in multidimensional well-being remains underexplored. We propose to address this issue by means of a multidimensional spatial model. We position the countries in the Euclidean K-dimensional space in which each dimension is a specific aspect of well-being, and we consider each individual's opinion on the same dimensions to calculate the personal optimal point. The distance between the optimal point of well-being and the actual observed point at individual level is the individuals' loss in well-being. We show that the societal loss at country-level is negatively related to the overall well-being and the main indices of quality of democracy. Based on the above evidence, we would argue that a multidimensional spatial framework represents a promising tool for the analysis of the whole class of multidimensional measures of well-being in which a group of individuals expresses the weights individually assigned to a set of dimensions within a pre-established range. Highlights: A multidimensional spatial model is proposed to evaluate multidimensional well-being. The distance between countries profiles and individual's opinion is interpreted as loss of well-being. Societal losses are negatively correlated to well-being and quality of democracy. Multidimensional spatial model is a promising framework for well-being assessment.